Cognition & Evolution: A Reply to Nagel’s Charges on the Evolutionary Explanation of Cognition - Jiang, Haiyu (Stance: an international undergraduate philosophy journal, 2017)
In this paper, I examine one of Nagel’s arguments against evolutionary theory, that the evolutionary conception of nature is incompatible with our understanding of cognition. I reconstruct Nagel’s two charges that the evolutionary conception of nature is at odds with our ability to acquire objective knowledge of the external world and that evolutionary theory is insufficient to explain logic’s absolute reliability. I reply to the first charge by suggesting that we should understand our ability to logically reason as a by-product instead of a direct product of the evolutionary processes. Then I reply to the second charge by denying that logic’s reliability is an appropriate subject of inquiry the evolutionary theory.